2022
DOI: 10.3390/ma15217556
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Modification of Titanium and Its Alloys for Medical Implants on Their Corrosion Behavior

Abstract: Titanium and its alloys are often used for long-term implants after their surface treatment. Such surface modification is usually performed to improve biological properties but seldom to increase corrosion resistance. This paper presents research results performed on such metallic materials modified by a variety of techniques: direct voltage anodic oxidation in the presence of fluorides, micro-arc oxidation (MAO), pulse laser treatment, deposition of chitosan, biodegradable Eudragit 100 and poly(4-vinylpyridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…The values are presented in Figure 6 c. Overall, it is evidenced that the uncoated titanium alloy substrate had the lowest corrosion rate owing to the stable and dense oxide layer on its surface, while the least corrosion-resistant sample was the dCP-PCL composite coated sample proving its fast bioresorption ability. These findings are in good agreement with other research works regarding the corrosion study of CaP-coated implant materials [ 86 , 87 , 88 , 89 , 90 ]. In a recent study, Pawłowski et al [ 86 ] thoroughly investigated the corrosion properties of different titanium alloy implants after various surface modifications, such as direct voltage anodic oxidation in the presence of fluorides, micro-arc oxidation (MAO), pulse laser treatment, deposition of chitosan, biodegradable polymers, carbon nanotubes, nanoparticles of TiO2, and chitosan with Pt (nano Pt).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The values are presented in Figure 6 c. Overall, it is evidenced that the uncoated titanium alloy substrate had the lowest corrosion rate owing to the stable and dense oxide layer on its surface, while the least corrosion-resistant sample was the dCP-PCL composite coated sample proving its fast bioresorption ability. These findings are in good agreement with other research works regarding the corrosion study of CaP-coated implant materials [ 86 , 87 , 88 , 89 , 90 ]. In a recent study, Pawłowski et al [ 86 ] thoroughly investigated the corrosion properties of different titanium alloy implants after various surface modifications, such as direct voltage anodic oxidation in the presence of fluorides, micro-arc oxidation (MAO), pulse laser treatment, deposition of chitosan, biodegradable polymers, carbon nanotubes, nanoparticles of TiO2, and chitosan with Pt (nano Pt).…”
Section: Resultssupporting
confidence: 93%
“…These findings are in good agreement with other research works regarding the corrosion study of CaP-coated implant materials [ 86 , 87 , 88 , 89 , 90 ]. In a recent study, Pawłowski et al [ 86 ] thoroughly investigated the corrosion properties of different titanium alloy implants after various surface modifications, such as direct voltage anodic oxidation in the presence of fluorides, micro-arc oxidation (MAO), pulse laser treatment, deposition of chitosan, biodegradable polymers, carbon nanotubes, nanoparticles of TiO2, and chitosan with Pt (nano Pt). They found that the corrosion current densities were in the region of some nA/cm 2 , and all the investigated surface modifications decreased the corrosion resistance.…”
Section: Resultssupporting
confidence: 93%
“…In a previous study, we also demonstrated the improvement of osseointegration of TiNbSn alloys anodized in a sulfuric acid electrolyte [ 21 , 22 ]. Anodic oxidation of titanium alloys has been reported to improve corrosion resistance and biocompatibility [ 45 , 46 , 47 , 48 ]. The anodic oxidation technique is expected to be a surface processing technology that can improve the function of titanium alloys.…”
Section: Discussionmentioning
confidence: 99%
“…TiNbSn alloys may be superior titanium alloys as substrates for anodic oxidation. The anodic oxidation of other titanium alloys, such as Ti6Al4V alloys, has also been reported to improve osseointegration, corrosion resistance, and biocompatibility [ 45 , 46 , 47 , 48 ]. Currently, only sulfuric acid anodization under high-voltage conditions has achieved both improved bone affinity and antibacterial performance, and the development and advancement of other anodization techniques is expected in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] surface reactions, while MAO is more expensive, not wellcommercialized and the design of coating properties is more difficult. 48 EPD is a bridge between two processes: deposition and electrophoresis. 49 The applied electric field enables the deposition of thick films or bulk components.…”
Section: Introductionmentioning
confidence: 99%